2022
DOI: 10.3389/fpsyt.2022.960648
|View full text |Cite
|
Sign up to set email alerts
|

The complex burden of determining prevalence rates of mild cognitive impairment: A systematic review

Abstract: Mild cognitive impairment (MCI) is a syndrome characterized by a decline in cognitive performance greater than expected for an individual's age and education level, but that does not interfere much with daily life activities. Establishing the prevalence of MCI is very important for both clinical and research fields. In fact, in a certain percentage of cases, MCI represents a prodromal condition for the development of dementia. Accordingly, it is important to identify the characteristics of MCI that allow us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 115 publications
1
22
0
1
Order By: Relevance
“…The detection of MCI and AD is limited in community settings [31-33] due in part to the use of brief screening tests of objective cognitive performance that lack psychometric properties similar to those of Gold Standard tests [4,34]. However, Gold Standard tests, such as the RBANS, are lengthy and require specialized staff to administer, score and interpret, making them impractical in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of MCI and AD is limited in community settings [31-33] due in part to the use of brief screening tests of objective cognitive performance that lack psychometric properties similar to those of Gold Standard tests [4,34]. However, Gold Standard tests, such as the RBANS, are lengthy and require specialized staff to administer, score and interpret, making them impractical in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of MCI and AD is limited in community settings [31][32][33] due in part to the use of brief screening tests of objective cognitive performance that lack psychometric properties similar to those of Gold Standard tests [4,34]. However, Gold…”
Section: Discussionmentioning
confidence: 99%
“…According to data presented in the ‘Dementia in Europe Yearbook 2019’, the number of people living with dementia in Italy was 1.3 million in 2018 and is expected to raise to 1.4–1.5 million by 2025, 50–70% of which facing AD (i.e., 0.7–1.1 millions) [ 21 , 22 ]. With regard to MCI, many authors reported a prevalence of 15–20% in the general population, with a rate of conversion to dementia of 10–15% per year [ 23 ]. In a 2008 Italian study, the prevalence of MCI in a population over the age of 65 was 7.7% (51% of which of the amnestic type), meaning 1,081,958 people in Italy suffering from MCI (551,799 with the amnestic type) [ 24 ].…”
Section: Epidemiologic Considerationsmentioning
confidence: 99%
“…The main limitation is that MCI is a varied phenomenon. In a recent systematic review [55], authors highlighted the difficulty of diagnosing MCI. They found that MCI prevalence rates range from 1.2 to 87%.…”
Section: Limits Implications and Suggestions For The Futurementioning
confidence: 99%